Estrus Induction And Serum Progesterone And Oestradiol-17β Profile In Norgestomet Primed Postpartum Anoestrus Surti Buffaloes - Parmar, S.C.; Khasatiya, C.T.; Tyagi, K.K.; Chaudhary, J.K.; Patel , R.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The study was conducted on eighteen postpartum anoestrus Surti buffaloes to evaluate the effect of Norgestomet ear implant alone and in combination with PMSG treatment on estrus induction and serum progesterone and oestradiol-17β profile. The buffaloes in Group-I and Group-II were treated with Crestar ear implant for 9 days together with 2 ml i/m injection of Crestar solution on the day of implant insertion. In Group-II, additionally 500 IU PMSG was given i/m on the day of implant removal, whereas the buffaloes in Group-III received 5 ml normal saline i/m on day 0 and 9 as a placebo and served as anoestrus control. The estrus was induced in cent per cent of buffaloes in Gr-I and Gr-II with mean estrus induction intervals of 2.56 ± 0.34 and 2.40 ± 0.29 days, respectively and the conception rate at induced estrus was highest (66.67 %) in Gr-II followed by Gr-I (33.33 %). In the Norgestomet treated groups a significant decreasing trend of endogenous progesterone concentration was observed at different time intervals of ear implant insertion. The mean serum oestradiol-17β levels gradually increased from the day of implant insertion to the day of induced estrus in the treatment groups and the values were found to be the highest on the day of estrus in the treatment Group-II followed by Group-I and the least in control Group-III. The linear increasing trend of mean serum oestrdiol-17β concentration observed over the period of time with Crestar ear implant alone and in combination with PMSG treatment indicated resumption of ovarian follicular activity and ovulation in anoestrus buffaloes.